2021
DOI: 10.1371/journal.pone.0254977
|View full text |Cite
|
Sign up to set email alerts
|

Facing the COVID-19 pandemic inside maternities in Brazil: A mixed-method study within the REBRACO initiative

Abstract: Introduction COVID-19 pandemic posed major challenges in obstetric health care services. Preparedness, development, and implementation of new protocols were part of the needed response. This study aims to describe the strategies implemented and the perspectives of health managers on the challenges to face the pandemic in 16 different maternity hospitals that comprise a multicenter study in Brazil, called REBRACO (Brazilian network of COVID-19 during pregnancy). Methods Mixed-method study, with quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…It can be observed that the increase in deaths by these causes coincided with the peaks of COVID-19 in the country ( S2 Table ). In general, the overloaded medical-hospital network (especially in the North and Northeast regions) [ 35 ], in addition to patients’ reluctance to go to health services during the pandemic due to fear of contamination by SARS-CoV-2, the increasing number of confirmed COVID-19 new cases among healthcare professionals, a lack of personal protective equipment, limited precautions against infection, or even premature deaths among healthcare professionals [ 15 , 36 ] may have diminished the already limited provision and utilization of maternal healthcare services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the increase in deaths by these causes coincided with the peaks of COVID-19 in the country ( S2 Table ). In general, the overloaded medical-hospital network (especially in the North and Northeast regions) [ 35 ], in addition to patients’ reluctance to go to health services during the pandemic due to fear of contamination by SARS-CoV-2, the increasing number of confirmed COVID-19 new cases among healthcare professionals, a lack of personal protective equipment, limited precautions against infection, or even premature deaths among healthcare professionals [ 15 , 36 ] may have diminished the already limited provision and utilization of maternal healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1990 and 1999, the number of maternal deaths in the country fell significantly, followed by a relatively stable pattern between 2000 and 2013, then a slight drop between 2017 and 2019 [10]. However, recent studies suggest a reversal in the decreasing pattern of maternal deaths [11][12][13] because of serious failings in the COVID-19 epidemic's management in Brazil [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The present research is part of a large prospective cohort study included in REBRACO – Brazilian Network of COVID-19 in Obstetrics – a multicenter study of 15 Brazilian referral centers from different regions across the country aiming to understand the burden of disease on maternal and perinatal outcomes related to COVID‐19 infection, with the University of Campinas (Unicamp) as coordinating center [ [14] , [15] ]. At Unicamp, SARS-CoV-2 quantitative reverse transcriptase polymerase-chain-reaction (RT-qPCR) assay testing for suspected cases started in April 2020 and routine universal screening was implemented in June 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Just as critically, there are significant concerns regarding the indirect effects of the pandemic on the access and availability of healthcare services, especially for women's health. Unlike other clinical conditions or elective procedures, obstetric care cannot be postponed, childbirth cannot be rescheduled, and low-resourced settings face a significant challenge in ascertaining proper care (Costa et al, 2021).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Continuous training programs, application of evidence-based protocols and cooperative initiatives and leadership are crucial to removing the fear of the virus and attaining adequate healthcare inside maternity and child wards, especially in low and middle-income settings. (Costa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%